Implikasi Hukum Penerbitan Covernote Perbankan Tanpa Akta Otentik Terhadap Tanggung Jawab Notaris Dalam Perspektif Perlindungan Konsumen - Stansyah, Dedy (Faculty of Law, University of Muhammadiyaha Surabaya, 2025)
This research analyzes the legal implications of issuing banking covernotes without authentic deeds, focusing on notary responsibility and consumer protection in Indonesia. Using a normative juridical method, this study examines regulations, legal principles, and relevant case studies to address the normative vacuum surrounding covernotes. The findings indicate that while covernotes function to expedite credit disbursement pending the completion of mortgage certificates, they lack the executory legal force of authentic deeds. Consequently, covernotes serve primarily as moral guarantees, leaving banks vulnerable during debtor defaults and exposing debtors to legal uncertainty regarding collateral status. The absence of specific regulations in the Notary Law (UUJN) creates significant risks for all parties. The study highlights that notaries bear full liability for the content of covernotes; negligence or falsification of information can lead to civil lawsuits for unlawful acts, administrative sanctions, and criminal charges for forgery. From a consumer protection perspective, the current reliance on covernotes places debtors in a weak position due to information asymmetry and a lack of binding legal protection. The research concludes that specific regulations are urgently needed to clarify the legal standing of covernotes, ensuring that the efficiency of banking transactions does not compromise legal certainty and justice for consumers and creditors alike